Reviewing the Benefits of Aging Populations: Care Activities Provided by the Older People as a Commons - Calvo-Sotomayor, Iñigo; Atutxa, Ekhi (Frontiers in Public Health, 2022)
This research reviews the commons paradigm as a framework for understanding the positive contribution of older cohorts to society. The commons, thought as instituting praxis that provide social goods based on autonomy and reciprocity, can help in understanding the role of this age group in providing care to the rest of society. This approach overturns the way economic literature approaches the aging phenomenon. What is understood as a ‘common evil’ — or a problem that needs to be solved — can be analyzed as a ‘common good’. From this perspective, older people (population aged 65 and over) are essential to European society and the economy to carry out informal care activities that enable and facilitate the ‘productive’ activities of working people.